HAK UNTUK MEMPEROLEH NAFKAH DAN WARIS DARI AYAH BIOLOGIS BAGI ANAK YANG LAHIR DARI HUBUNGAN LUAR KAWIN DAN PERKAWINAN BAWAH TANGAN - Saraswati, Bellana; Sekar, I Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
Article 43 paragraph (1) the Act No. 1 Year 1974 Concerning Marriage determine that an illegitimate child only has a civil relationship with her mother and her mother's family. Though these provisions may result in various losses for the child. Until finally the various losses now can be minimized through the Constitutional Court Decision No. 46/PUU-VIII/2010, which is then reinforced with the Supreme Court Circular Letter No. 07 Year 2012. Therefore, this paper will describe the legal relationship between an illegitimate child with his biological father in accordance with the Constitutional Court Decision No. 46/PUU-VIII/2010 as well as the rights that can be obtained under the law relationships contained in the Supreme Court Circular Letter No. 07 Year 2012.
Keywords: Living, Heir, Illegitimate Child, Unregistered Marriage